Serum testosterone concentration in surgically castrated Black Bengal goats (Bangladesh Veterinarian, 2018)
The experiment was carried out to detect the blood serum testosterone concentration after orchiectomy in Black Bengal bucks (Capra hircus). Twelve apparently healthy bucks of 8 - 10 months old were randomly divided into two groups. Group A were castrated surgically through open uncover method and group B remained intact. Local analgesia (2% lidocaine hydrochloride) @ 0.5 mL per spermatic cord and 0.5 mL at the tip of each scrotum were applied initially in all bucks. After aseptic preparation, incision was given at the tip of the scrotum and tunica vaginalis was incised to exteriorize the testis. Anchoring was done at the spermatic cord followed by orchiectomy. The scrotal raphe was incised to reach the other testis and the same procedure was followed. Blood samples were collected from jugular vein before orchiectomy and on day 30. In the castrated bucks, serum testosterone concentration was significantly (P